Grundrechte Klausur- und Examensfälle - Valentine, Dana-Sophia; Petras, Maximilian (De Gruyter Studium, 2022)
This casebook takes an innovative approach to address the basic rights granted by the German constitution. A team of young scholars from all over Germany has combined basic knowledge for students with more in-depth knowledge for state examination candidates in practical exercise cases. Students can read up on background knowledge in the freely available textbook and comment on all texts on a digital platform.